2022
DOI: 10.1021/acsmacrolett.2c00620
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Charge Composition and Distribution on the Antibacterial Properties of Polypeptide Coatings

Abstract: Inspired by the charge composition and distribution of proteins and peptides, we designed and prepared a series of brush polypeptides with positive and negative charges separately distributed in the side chains and the backbones. The brush polypeptides can self-or co-deposit on various substrates forming ultrathin and stable coatings. They showed potent bactericidal activity and antibiofilm property, outperforming conventional linear polypeptide coatings with randomly distributed positive and negative charges.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Increasing DS or KE length slightly improved the inhibition of biofilm growth. It is worth mentioning that K 25 E 25 -coated PDMS surfaces showed 30% biofilm growth after 48 h, which is much higher than K 50 E 50 coatings (about 4%) from our recent work . We reasoned that the decreased main-chain length and DA-assisted codeposition method have led to faster biofilm growth on material surfaces since the PDA-coated surfaces have showed increased biofilm growth.…”
mentioning
confidence: 70%
See 4 more Smart Citations
“…Increasing DS or KE length slightly improved the inhibition of biofilm growth. It is worth mentioning that K 25 E 25 -coated PDMS surfaces showed 30% biofilm growth after 48 h, which is much higher than K 50 E 50 coatings (about 4%) from our recent work . We reasoned that the decreased main-chain length and DA-assisted codeposition method have led to faster biofilm growth on material surfaces since the PDA-coated surfaces have showed increased biofilm growth.…”
mentioning
confidence: 70%
“…Recently, bifunctional antibacterial polymer coatings have gained increasing attention for their diversity of chemical and topological structures, development of controlled polymerization methods, and good processability which enable them to possess tunable and desired surface biological properties. Usually, these coatings are composed of two distinct functional components (e.g., chemical groups or chain segments) with antifouling or bactericidal properties. Different functional components can be distributed in linear polymers with random or block sequences or separately distributed in the side-/main-chains to optimize surface biological properties, such as antifouling and bactericidal properties. Previous work has suggested that hydrogen bonding hydration from both pendant groups and main-chains can improve the antifouling property of hydrogels .…”
mentioning
confidence: 99%
See 3 more Smart Citations